CA-125 requisition pattern in a tertiary care hospital in central India and necessary modifications - Amle, Dnyanesh B; Verma, Neha Rani; Bhargava, Piyush; Rathore, Sudama; Tirkey, Neelam B; Patra, Pradeep Kumar (Asian Journal of Medical Sciences, 2017)
Background: Utility of CA-125 is not limited to being tumour marker for only epithelial ovarian carcinoma but it has also been found to be elevated in various other benign and malignant conditions. This versatility also adds to increased prescription of CA-125 in non ovarian tumours and is also a reason for reduced specificity of CA-125 as tumor marker for epithelial ovarian cancer. Both these factors could lead to inappropriate frequent prescription and missed diagnosis. Aims and Objective: We thus carried out a case note audit aimed to assess the prescription pattern of CA-125 in daily clinical practice and its contribution to final diagnosis and management in a tertiary healthcare facility in central India. Materials and Methods: All the subjects advised estimation of CA 125 during the study period were included in the study. Data regarding sign and symptoms, provisional diagnosis was collected and serum CA-125 levels estimated. Result: Total 238 subjects were recruited for the study, out of them 221 (92.8%) were female and 17 (7.2%) were male. Mean age was found to be 43.95±13.88. S. CA-125 level were 32.30(3.24-5000) U/ml. Only 65% investigations were related to ovarian carcinoma and out of that abnormal CA125 levels were noted in 54% subjects. No oblivious indication was found in 14% subjects. Abnormal CA-125 levels were significantly low in frequency in follow up subjects as well as in subjects with no indication. Conclusion: Low specificity and versatility of CA-125 in diagnosis of various benign and malignant conditions may lead to inappropriate prescription of CA-125. This may cause additional economic burden as well as psychological stress to patients. This can be avoided by establishment of proper algorithm or guidelines to advice tumor markers and their strict implementation. Asian Journal of Medical Sciences Vol.8(5) 2017 17-21